Analisis Perkembangan Peserta Didik Anak Sekolah Dasar Kelas 1 di SD IT Al Hijrah 2 Laut Dendang - Ramadhan Lubis; Masriana Masriana; Yunizar Ritonga; Nurul Hasanah; Nurul Dinda Aulia; Aulia Rahman; Risma Handayani; Alda Putriana (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to determine the development of grade 1 elementary school students in learning. The method used in this study is qualitative with a descriptive study design. The research uses data collection techniques with direct observation, interviews, and documentation. The research location is at SD IT Al-Hijrah 2, Jl. Perangkaan, Deli Serdangn, with the research subjects involving grade 1 elementary school children and also grade 1 teachers. Based on the results of the research obtained, significant physical development, which at their age has experienced increased weight growth, experienced milk teeth change and height growth. The intellectual development of the child begins to show their logical thinking ability and understand other people's points of view. Emotional and social development can be seen when they can receive and understand the advice or input given by the teacher, such as at school. Furthermore, related to children's moral development, including understanding the rules in the classroom, the rules of making friends, communicating with teachers and they understand the consequences of their actions.